If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6k-9=3k+9
We move all terms to the left:
6k-9-(3k+9)=0
We get rid of parentheses
6k-3k-9-9=0
We add all the numbers together, and all the variables
3k-18=0
We move all terms containing k to the left, all other terms to the right
3k=18
k=18/3
k=6
| 4x-32=3x+6 | | -7/3u=21 | | 2x-1.5=31.8 | | 6a-a-4a=8 | | 13=k4 | | 9t+7=3t+19 | | -78=-6f | | -4(4u-2)+8u=4(u+6) | | 4j+4=3j+11 | | 3.6n+2.3n=25.3+10.1 | | 8u-8u+u=6 | | -12=v+7 | | 6(4b+4)=0 | | (9x-1)=(8.5x+2) | | 6x+3−3x=0 | | 3n.n=11 | | 15=3+4d | | x=3+1/4 | | -15/2=60/x | | m+487 =9m= | | −34a=−9 | | -2(b+5)-3=11 | | 6(x/2-3)+10=-32 | | 8i-6=5i+6 | | 9y+3•(-3y+6)=18 | | 16z-6z-z=9 | | 2(m-160=44 | | 9x+8=11x8 | | 13=y/2+9 | | 3(q+9)=99 | | 36y=2 | | 8d-7=2d+17 |